PENGARUH ISLAMIC GOVERNANCE SCORE, LEVERAGE DAN PROFITABILITAS TERHADAP ISLAMIC SOCIAL REPORTING INDEXPADA BANK UMUM SYARIAH DI INDONESIA - TAUFIK .; MARLINA WIDIYANTI; RAFIQOH . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aims to analyze the influence of Islamic Governance Score, Leverage and Profitability to Islamic Social Reporting Index banks In Indonesia. The population used in this study consists of 11 Islamic period 2010 – 2013. Purposive sampling was implemented in this research. Off 11 banks, 8 banks are carried out as a sample. Multiple regression analysis was used to know the impact of Islamic Governance Score, Leverage and Profitability to Islamic Social Reporting Index banks In Indonesia. The result showed that partially Islamic Governance Score, Leverage have no impact to Islamic Social Reporting Index, while profitability has positif and significant effect to Islamic Social Reporting Index. Simultaneously, Islamic Governance Score, Leverage and Profitability have impact to Islamic Social Reporting Index. For further research, it is expeted to add other variables effecting Islamic Social Reporting Index.